A note on the reply of the manuscript of Aly R. Seadawy et al. [Superlattices and Microstructures, in press]. (August 2018) - Zayed, Elsayed M.E.; Al-Nowehy, Abdul-Ghani; Alngar, Mohamed E.M.; Shohib, Reham M.A.
Abstract: In this note, we show that the above reply of the manuscript of the authors [1] is incorrect. So, the new extended auxiliary equation method (Khater method) obtained in [3, 4] is wrong. Consequently, all the exact solutions of the given evolution equations in [3, 4] are not true. Highlights: We show that the above reply is incorrect. We show that the authors of reply do not write the truth. We show that new auxiliary equation method (Khater method) is wrong. We compare between the original comment and the wrong reply.